Lemna minor, a hyperaccumulator shows elevated levels of Cd accumulation and genomic template stability in binary application of Cd and Ni: a physiological and genetic approach - ÖZYİĞİT, İBRAHİM İLKER (TAYLOR & FRANCIS INC, 2021)
In this study, to determine whether having potential to be used as hyperaccumulator for Cd and Ni, numerous experiments were designed for conducting assessments for physiological and genotoxic changes along with defining possible alterations on mineral nutrient status of Lemna minor L. by applying Cd-Ni binary treatments (0, 100, 200 and 400 mu M). Our study revealed that there were increases in the concentrations of B, Cr, Fe, K, Mg, and Mn whereas decreases were noticed in the concentrations of Na and Zn and the levels of Ca were inversely proportional to Cd-Ni applications showing tendency to increase at the low concentration and to decrease at the high concentration. Randomly Amplified Polymorphic DNA (RAPD) and Inter Simple Sequence Repeat (ISSR) analyses revealed that rather than band losses and new band formations, mostly intensity changes in the band profiles, and low polymorphism and high genomic template stability (GTS) were observed. Although, to date, L. minor was defined as an efficient hyperaccumulator/potential accumulator or competent phytoremedial agent by researchers. Our research revealed that L. minor showing high accumulation capability for Cd and having low polymorphism rate and high genomic template stability is a versatile hyperaccumulator, especially for Cd; therefore, highly recommended by us for decontamination of water polluted with Cd. NOVELTY STATEMENT Many studies have been focused on the effects of individual metal ions. However, heavy metal contaminants usually exist as their mixtures in natural aquatic environments. Especially, Cd and Ni coexist in industrial wastes. In this study, the accumulation properties of Lemna minor for both Cd and Ni were investigated and the effects of Cd and Ni on the bioaccumulation of B, Ca, Cu, Fe, Mg, K, Mn, Na, Pb and Zn in L. minor were also determined. This study furthermore aimed to assess the genotoxic effects of Cd and Ni found in being extended concentrations on DNA using the Randomly Amplified Polymorphic DNA-Polymerase Chain Reaction (RAPD-PCR) method.
Keywords: Heavy metals; genotoxicity; nutritional elements; duckweed; RAPD-ISSR; HEAVY-METAL; CADMIUM TOLERANCE; NICKEL; PLANTS; TOXICITY; PHYTOREMEDIATION; DETOXIFICATION; GERMINATION; DIVERSITY; EXPOSURE